Ketahanan beberapa genotipe ubi jalar ( Ipomoea batatas L. ) terhadap hama boleng Cylas formicarius Fabricus - Kristina Uviani Samosir; Yacob Bodang; Yohanis Amos Mustamu; Herman Wafom Tubur; Rizald Hussein (Agrotek, 2021)
The aim of this study was to measure the resistance of several sweet potato genotypes to C. formicarus Fabricus (Coleoptera: Curculionidae) attack. The design used in this study was a randomized block design (RAK) with 9 treatments and 3 replications, so that 27 experimental units were obtained. The genotype treatmens were Antin 1, Antin 2, Antin 3, Koya 2, Koya 4, Koya 6, Beta 2, Kidal, and Salosa. The results of the analysis showed that all of the tested genotypes were naturally damaged by C. formicarius pests both at the base of the stem and on the tubers. The intensity of tuber damage caused by C. formicarius among 9 tested genotypes was the highest in the Salosa genotype (17.593%) and the lowest was in the Antin 1 genotype (5.553%). The intensity of damage to the base of the stem caused by C. formicarius among the 9 genotypes tested was the highest in the Antin 1 genotype (61.110%) and the lowest was in the Left-handed genotype (47,333%). Colonization (infestation) of C. formicarius in the test genotype occurred from the beginning of the observation at 4 week until the plants were harvested (tubers formed). The egg and larvae populations in this study were not found, while the number of imago from each test genotype was different with the highest population was in the Antin 1 genotype (3,3200 individuals), then the lowest imago population was in the Antin 3 and salosa genotypes with an average value of 2.1467 individuals. The resistant genotypes were Koya 4, Salosa, and Beta 2, while genotypes that were moderately resistant were Koya 2, Kidal, Antin 3, but Antin 2, Koya 6 and Antin 1 were sensitive genotypes.